Observation of partonic flow in proton-proton and proton-nucleus collisions - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (NATURE PORTFOLIO, 2026)
Quantum Chromodynamics predicts a phase transition from hadronic matter to quark-gluon plasma (QGP) at high temperatures and energy densities, where quarks and gluons (partons) are no longer confined within hadrons. The QGP forms in ultrarelativistic heavy-ion collisions. Anisotropic flow coefficients, quantifying the azimuthal expansion of produced matter, probe QGP properties. Flow measurements in high-energy heavy-ion collisions show a distinctive grouping of anisotropic flow for baryons and mesons at intermediate transverse momentum - a feature associated with flow imparted at the quark level, confirming QGP existence. The observation of QGP-like features in proton-proton and proton-ion collisions has sparked debate about QGP formation in smaller systems. For the first time, we demonstrate the distinctive grouping of anisotropic flow for baryons and mesons in high-multiplicity proton-lead and proton-proton collisions at the Large Hadron Collider (LHC). These results are described by a model including hydrodynamic flow followed by hadron formation via quark coalescence, consistent with the formation of partonic flowing systems in these collisions.
Keywords: COLLECTIVITY; ANISOTROPY; EXPANSION; Science & Technology - Other Topics